Manufacturing method of hierarchical porous structure cell self-adaptive growth type bone repair scaffold
The collagen fiber network is constructed through the selection laser thawing technology to build through macropores and freeze-drying technology, which solves the problem that a single pore structure cannot meet the needs of osteogenesis and vascularization, and realizes a bone repair scaffold with a graded porous structure, which improves cell adhesion and bone Integration capability.
Patent Information
- Application Number
- CN202311691210.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-11
- Publication Date
- 2024-12-13
AI Technical Summary
The single pore structure of existing bone repair scaffold materials cannot meet the different needs of osteogenesis and vascularization, or the engineering assembly of cells of different scales, and cannot obtain the graded porous structure in one step in the same space.
The SLM porous titanium scaffold is constructed through the macropore by selective laser melting technology, and the collagen fiber micron-level network structure is constructed in the macropore through freeze-drying technology, which simulates the multi-level structure of human bone, and realizes the adaptive growth bone repair of hierarchical porous structures. Bracket.
By constructing a network structure through macropores and collagen fibers, it provides more cell adhesion sites and pseudopodosal spreading support, promotes osteogenesis rate and angiogenesis, meets the engineering assembly needs of cells at different scales, and improves osteointegration and angiogenesis capabilities.
Smart Images

Figure CN119113202A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing, and in particular to a method for manufacturing a hierarchical porous structure cell adaptive growth type bone repair scaffold. Background Art
[0002] Bone is a complex system with rich functions and multi-level structure and composition. Studies have shown that bones can be divided into nine levels from macroscale, microscale to nanoscale. Bone tissue is mainly composed of cells and extracellular matrix, including organic matrix (collagen fibers, amorphous matrix) and inorganic matrix (hydroxyapatite, bone salt). In order to reproduce the anatomical structure and composition of natural bone, scaffold materials are currently developing towards hierarchical porous structures and composite matrix compositions.
[0003] For the repair of large bone defects, researchers have been exploring the effects of through holes of different sizes (106-212μm, 212-300μm, 300-400μm, 400-500μm and 500-600μm) on the osteogenic and angiogenic abilities of scaffolds to define the most reasonable pore size. Some studies have found that new bone is generated on large-pore (≧350μm) scaffolds, while only cartilage is formed on small-pore (≦120μm) scaffolds; some studies have also found that the bone formation rate of the scaffold is affected when the pore size is too large (≧400μm). It can be seen that the most reasonable pore size obtained by different research works is different. The reason is that the structure and composition of human bones themselves are very complex. It is a multi-scale hierarchical porous structure, and a single structure cannot meet the requirements of bone regeneration.
[0004] In addition, bone marrow mesenchymal stem cells (BMSCs), endothelial progenitor cells (EPCs) and the like are mostly adherent cells, so more anchor points are needed during cell migration and proliferation to increase the contact rate between the cells and the three-dimensional surface of the scaffold. If the cells cannot adhere to the entire surface of the scaffold, space will be reserved for the growth of bacterial biofilms. With the expression and accumulation of adhesion proteins, cells form tightly adhered cell layers or cell spheres, requiring larger pore scaffolds to provide space for cell growth and metabolism. At this time, the small pores that provided more anchor points for cell adhesion in the early stage will limit the growth of cell layers or cell spheres into the porous structure. It can be seen that a single-structure scaffold cannot meet the engineering assembly of cells of different scales.
[0005] Currently, the main preparation methods for porous scaffolds include 3D printing, electrospinning, and freeze-drying. These technologies alone cannot obtain a hierarchical porous structure in one step in the same space.
[0006] In the public literature, for example, the paper "Study on the Performance of 3D Printed Porous Titanium Alloy Silk Fibroin Hydrogel Coating" uses 3D printing technology to prepare porous titanium alloy implant specimens, sandblasts the specimens and ultrasonically cleans them, uses photocuring to form silk fibroin hydrogel on the surface and inside the pores of the porous titanium alloy, and performs surface characterization and evaluation on the formed hydrogel. Hydrogels are not porous structures, so this method cannot obtain multi-scale porous structures.
[0007] Another example is the paper "Study on Mechanical and Biological Properties of 3D Printed TPMS Gradient Porous Titanium Alloy Structures", which uses a three-periodic minimal surface structure (TPMS) to design two porous scaffolds with porosity gradients in different directions to simulate the biomechanical properties of bones, and designs a uniform porous scaffold as a control. This method also cannot obtain a graded porous structure, and the gradient porous structure is all macroscopic pores.
[0008] For the repair of large bone defects, researchers have been exploring the effects of pores of different sizes (106-212μm, 212-300μm, 300-400μm, 400-500μm and 500-600μm) of scaffold materials used for bone repair on the ability to form bones and blood vessels, in order to define the most reasonable pore size. However, studies have shown that scaffolds with a single pore structure cannot meet the different needs of bone formation and blood vessel formation, as well as the engineering assembly needs of cells of different scales. This is because the structure of human bones itself is very complex, and is a multi-scale hierarchical porous structure.
[0009] The shortcomings of the existing technology or the technical problems that need to be solved urgently are that the single pore structure of the bone repair scaffold material cannot meet the different needs of osteogenesis and angiogenesis, or the engineering assembly of cells of different scales. The ideal bone repair scaffold material should meet the following requirements: in the early stage, it has a microporous structure with low porosity and a composition similar to that of ECM, which can provide more active sites for cell adhesion and support points for pseudopodia spreading; in the later stage, it has a macroscopic macroporous structure and a composition that promotes mineralization, providing space for tightly adhered cells to grow into the hollow structure, and promoting angiogenesis and osteogenesis mineralization. The main preparation methods of porous scaffolds currently include 3D printing, electrospinning, freeze-drying and other technologies, which cannot obtain a graded porous structure in the same space in one step. Summary of the invention
[0010] Based on the technical problems existing in the background technology, the present invention proposes a method for preparing a hierarchical porous structure cell adaptive growth type bone repair scaffold. Combined with the metal 3D printing technology, macroscopic through pores are first constructed, and the through pores are beneficial to tissue oxygen supply, nutrient supply, waste metabolism and angiogenesis; then the three-dimensional surface of the 3D printed porous titanium scaffold is hydrophilicized, and the freeze-drying technology is used to construct a collagen fiber micron-level network structure on the hydrophilic surface within the macroscopic pores, finally obtaining a bone-mimicking scaffold material in structure, composition and space.
[0011] The present invention provides a method for manufacturing a hierarchical porous structure cell adaptive growth type bone repair scaffold, comprising the following steps:
[0012] S1. Prepare SLM porous titanium stents with through-holes by selective laser melting technology. Design through-holes for suitable blood vessel growth. Combine metal selective laser melting technology with laser forming. Change the forming tilt angle, laser power, scanning speed, and scanning spacing parameters of the laser processing production process to obtain a through-hole structure.
[0013] S2, SLM porous titanium surface anodization preparation TiO2 nanotubes, porous titanium bracket samples were deoiled with acetone, ethanol, and deionized water, and pickled with a solution of HF acid and HNO3 acid under ultrasonic conditions, and finally cleaned and dried; porous titanium bracket was used as anode and platinum mesh as cathode, TiO2 nanotubes were prepared on the porous titanium three-dimensional surface by coaxial oxidation method, and the morphology of nanotubes was controlled by adjusting the voltage and oxidation time parameters of anodization;
[0014] S3, Preparation of SLM porous titanium-mineralized collagen hierarchical porous structure, using freeze-drying to construct a micron-scale type I collagen fiber network in the macro-scale SLM porous titanium to simulate the multi-layer structure of human bone; using the biomimetic mineralization method, Ca-GP and CaCl2 were used as calcium and phosphorus sources on the surface of collagen fibers to deposit degradable nano-HAP to simulate the composition of ECM and bone matrix.
[0015] Preferably, in step S1, the raw material titanium metal powder selected is TA2 metal powder with a particle size of 20-40 μm and a purity of >99.5%.
[0016] Preferably, in step S1, the pore size of the through-macroporous porous titanium is a pore size gradient structure, and the pore size changes from large to small along the thickness direction. The external coarse pore layer structure is a uniform three-dimensional space connected porous structure with a pore size of 500-600μm, a prism thickness of 100-150μm, and a porosity of 70-90%; the inner fine pore layer structure is a uniform three-dimensional space connected porous structure with a pore size of 200-300μm, a prism thickness of 100-150μm, and a porosity of 50-70%.
[0017] Preferably, in step S1, the laser power is 90W-100W, the laser scanning speed is 380-420mm / s, the scanning spacing is 55-65μm, the spot diameter is 70-80μm, and the surface micron-level spherical powder particle size and spacing of the material are observed using a scanning electron microscope.
[0018] Preferably, in step S1, after printing, the product is ultrasonically cleaned to remove excess powder remaining on the surface and then dried at room temperature.
[0019] Preferably, the step S2 specifically includes the following steps:
[0020] S21, degreasing, immersing the SLM porous titanium bracket sample in 50 ml acetone, ethanol, and deionized water respectively, treating it under ultrasonic conditions for 10 to 30 min, taking out the sample and rinsing it with deionized water;
[0021] S22, acid erosion, 5~15mL·L -1 HF and 10~30mL·L -1 HNO3 is prepared into an acid leaching solution, HF:HNO3:H2O=1:4:5, the deoiled sample is placed in the acid leaching solution, cleaned under ultrasonic conditions for 20~40s, taken out and rinsed with deionized water under ultrasonic conditions to remove the residual acid on the surface, dried naturally and set aside;
[0022] S23, preparation of anodizing electrolyte solution;
[0023] S24. Preparation of TiO2 nanotube film by anodization.
[0024] Preferably, the preparation method of the anodizing electrolyte solution in step S23 is:
[0025] Use a pipette to take 1-3 ml HF and 2-5 ml deionized water, add them to 90-95 ml diethylene glycol solvent, let the electrolyte stand for 10 minutes, stir it magnetically at 300-500 r / min for 30 minutes, mix the electrolyte thoroughly and evenly, and stabilize the temperature at 10-40°C.
[0026] Preferably, the method for preparing the TiO2 nanotube film by anodization in step S24 is:
[0027] S241, using the SLM titanium implant as the working electrode and the platinum mesh as the counter electrode, immersing the sample in the electrolyte prepared in step 23 under the condition of a magnetic stirring speed of 300 to 500 r / min;
[0028] S242, apply a constant potential of 40V to 100V, and anodic oxidation for 2h to 12h, and the experimental temperature is always stable at 10 to 40°C;
[0029] S243. Rinse the surface of the sample obtained by anodization with deionized water for 10 to 15 times and dry it at 50 to 70°C.
[0030] Preferably, the step S3 specifically includes the following steps:
[0031] S31, pretreatment, ultrasonication in acetone for 10 min, rinsing with deionized water three times, and drying at room temperature;
[0032] S32, adjust the pH of type I collagen to neutral with glacial acetic acid, slowly add ALP solution, slowly stir for 30 minutes, and put the mixture with ALP solution into a dialysis bag, seal it and transfer it to a mixed solution of Ca-GP and CaCl2, Ca:P=1.67, after temperature change at 37°C, mineralize for 24h, 48h and 72h respectively, the collagen self-assembles into collagen fibers to form a gel;
[0033] S33, the self-assembled type I collagen was ultrasonically cleaned with deionized water, and placed together with the SLM porous titanium scaffold in a homemade mold, and then placed in a -80°C refrigerator overnight, and freeze-dried in a freeze dryer to obtain a HAP-collagen-porous titanium scaffold;
[0034] S34, adjusting the concentration of the collagen solution to control the porosity and pore size of the collagen fibers;
[0035] S35. Use UV, XRD, XPS and FT-IR to detect the characteristic elements, crystal structure and groups of collagen and HAP in the porous titanium scaffold.
[0036] Compared with the existing technology, the beneficial effects of the present invention are as follows: a macroscopic through-pore porous titanium metal scaffold is first constructed by 3D printing technology, and the through-pores are beneficial to tissue oxygen supply, nutrient supply, waste metabolism and angiogenesis; then the three-dimensional surface of the 3D printed porous titanium scaffold is subjected to surface hydrophilic treatment, and the hydrophilic treatment is beneficial to the subsequent construction of a collagen fiber network; freeze-drying technology is used to construct a type I collagen fiber micron-scale network structure on the hydrophilic surface within the macroscopic pores. Collagen is the most abundant type of protein in mammals, and has good physical compatibility and biodegradability. It can provide more sites for cell adhesion, improve the osteogenesis rate and the bone integration of the scaffold surface and the surrounding tissues; since the degradation rate of collagen is controllable, it can provide space and the required active ingredients for later angiogenesis and osteogenic differentiation after degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Comparison of total protein content and ALP activity of MC3T3 cells cultured on SLM-Ti and COL-SLM-Ti surfaces for 7 and 14 days. DETAILED DESCRIPTION
[0038] The present invention will be further explained below in conjunction with specific embodiments.
[0039] Example
[0040] This embodiment proposes a method for preparing a hierarchical porous structure cell adaptive growth bone repair scaffold, which specifically includes the following three steps:
[0041] Step S1: Prepare a SLM porous titanium bracket with through-holes by using the selective laser melting technology.
[0042] Before printing, the raw material titanium metal powder was screened, and TA2 metal powder (particle size 20-40 μm) was used (purity > 99.5%).
[0043] Then the three-dimensional model is designed and laser processed. The pore structure parameters such as pore shape, porosity, pore size and pore size distribution have a great influence on osteogenesis and angiogenesis. The through-hole macroporous titanium designed in this embodiment adopts a pore gradient structure, that is, the pore size changes from large to small along the thickness direction. The external coarse pore layer structure is a uniform three-dimensional space connected porous structure with a pore size of 500-600μm, a prism thickness of 100-150μm, and a porosity of 70-90%. The inner fine pore layer structure is a uniform three-dimensional space connected porous structure with a pore size of 200-300μm, a prism thickness of 100-150μm, and a porosity of 50-70%.
[0044] During printing, the process parameters were adjusted, including laser power of 100W, laser scanning speed of 400mm / s, scanning spacing of 60μm, and spot diameter of 75μm. The surface morphology of the material (surface micron-level spherical powder particle size and spacing) was observed using a scanning electron microscope.
[0045] After printing, the product is ultrasonically cleaned to remove excess powder remaining on the surface and dried at room temperature.
[0046] Step S2, preparing TiO2 nanotubes by anodizing the surface of SLM porous titanium, specifically comprising the following steps:
[0047] Step S21, degreasing: The SLM porous sample is immersed in 50 ml of acetone, ethanol, and deionized water respectively, treated under ultrasonic conditions for 10 to 30 minutes, and the sample is taken out and rinsed with deionized water.
[0048] Step S22: Acid etching. 5-15 mL·L -1 HF and 10~30mL·L -1HNO3 was prepared into an acid immersion solution (HF:HNO3:H2O=1:4:5), and the deoiled samples were placed in the acid immersion solution and cleaned under ultrasonic conditions for 20 to 40 seconds. After being taken out, they were rinsed with deionized water under ultrasonic conditions to remove the residual acid on the surface, and then dried naturally for later use.
[0049] Step S23, preparation of anodizing electrolyte solution. Use a pipette to take 1-3 ml HF and 2-5 ml deionized water, respectively, and add them to 90-95 ml diethylene glycol solvent. Let the electrolyte stand for 10 minutes, and stir it magnetically at 300-500 r / min for 30 minutes to fully mix the electrolyte and stabilize the temperature at 10-40°C.
[0050] Step S24, prepare TiO2 nanotube film by anodization. Use SLM titanium implant as working electrode and platinum mesh as counter electrode. Immerse the sample in electrolyte under the condition of magnetic stirring speed of 300-500r / min. Apply a constant potential of 40V-100V and anodize for 2h-12h, and the experimental temperature is always stable at 10-40°C. Rinse the surface of the sample obtained by anodization with deionized water for 10-15 times and dry at 50-70°C.
[0051] Step S3, a method for preparing a SLM porous titanium-mineralized collagen hierarchical porous structure, specifically comprising the following steps:
[0052] Step S31, pretreatment: ultrasonicate in acetone for 10 minutes, rinse with deionized water for 3 times, and dry at room temperature.
[0053] Step S32, adjust the pH of type I collagen to neutral with glacial acetic acid, slowly add ALP solution, slowly stir for 30 minutes, and put the mixture with ALP solution into a dialysis bag, seal it and transfer it to a mixed solution of Ca-GP and CaCl2 (Ca:P=1.67). After the temperature changes at 37°C and mineralization for 24h, 48h and 72h respectively, the collagen self-assembles into collagen fibers to form a gel.
[0054] Step S33, ultrasonically clean the self-assembled type I collagen with deionized water, put it into a homemade mold together with the SLM porous titanium scaffold, and then place it in a -80°C refrigerator overnight, freeze-dry it in a freeze dryer to obtain a HAP-collagen-porous titanium scaffold. Adjust the concentration of the collagen solution to control the porosity and pore size of the collagen fibers. Use UV, XRD, XPS and FT-IR to detect the characteristic elements, crystal structure and groups of collagen and HAP in the porous titanium scaffold.
[0055] After SLM porous titanium constructed type I collagen fibers inside, the results of the osteoblast proliferation experiment on its surface showed that after MC3T3 cells were cultured on the SLM-Ti and COL-SLM-Ti surfaces for 7 and 14 days, the cell differentiation was detected by ALP activity and total protein content. Figure 1 After 7 and 14 days of culture, the ALP activity and total protein content of COL-SLM-Ti were significantly higher than those of SLM-Ti with a single porous structure.
[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a hierarchical porous structure cell adaptive growth type bone repair scaffold, characterized in that: The following steps are involved: S1. Prepare SLM porous titanium stents with through-holes by selective laser melting technology. Design through-holes for suitable blood vessel growth. Combine metal selective laser melting technology with laser forming. Change the forming tilt angle, laser power, scanning speed, and scanning spacing parameters of the laser processing production process to obtain a through-hole structure. S2, SLM porous titanium surface anodization preparation TiO2 nanotubes, porous titanium bracket samples were deoiled with acetone, ethanol, and deionized water, and pickled with a solution of HF acid and HNO3 acid under ultrasonic conditions, and finally cleaned and dried; porous titanium bracket was used as anode and platinum mesh as cathode, TiO2 nanotubes were prepared on the porous titanium three-dimensional surface by coaxial oxidation method, and the morphology of nanotubes was controlled by adjusting the voltage and oxidation time parameters of anodization; S3, Preparation of SLM porous titanium-mineralized collagen hierarchical porous structure, using freeze-drying to construct a micron-scale type I collagen fiber network in the macro-scale SLM porous titanium to simulate the multi-layer structure of human bone; using the biomimetic mineralization method, Ca-GP and CaCl2 were used as calcium and phosphorus sources on the surface of collagen fibers to deposit degradable nano-HAP to simulate the composition of ECM and bone matrix.
2. The method for preparing a hierarchical porous structure cell adaptive growth bone repair scaffold according to claim 1, characterized in that: In the step S1, the raw material titanium metal powder selected is pure Ti metal or titanium alloy, with a particle size of 20-40 μm and a purity of >99.5%. The pure Ti metal includes TA1, TA2, TA3, and TA4, and the titanium alloy is Ti-6Al-4V.
3. The method for preparing a hierarchical porous structure cell adaptive growth bone repair scaffold according to claim 1, characterized in that: In the step S1, the pore size of the through-hole macroporous titanium is a pore size gradient structure, and the pore size changes from large to small along the thickness direction. The external coarse pore layer structure is a uniform three-dimensional space connected porous structure with a pore size of 500-600μm, a prism thickness of 100-150μm, and a porosity of 70-90%; the inner fine pore layer structure is a uniform three-dimensional space connected porous structure with a pore size of 200-300μm, a prism thickness of 100-150μm, and a porosity of 50-70%.
4. The method for preparing a hierarchical porous structure cell adaptive growth bone repair scaffold according to claim 1, characterized in that: In the step S1, the laser power is 90W-100W, the laser scanning speed is 380-420mm / s, the scanning spacing is 55-65μm, the spot diameter is 70-80μm, and the surface micron-level spherical powder particle size and spacing of the material are observed using a scanning electron microscope.
5. The method for preparing a hierarchical porous structure cell adaptive growth bone repair scaffold according to claim 1, characterized in that: In the step S1, after printing, the product is ultrasonically cleaned to remove excess powder remaining on the surface and then dried at room temperature.
6. The method for preparing a hierarchical porous structure cell adaptive growth bone repair scaffold according to claim 1, characterized in that: The step S2 specifically includes the following steps: S21, degreasing, immersing the SLM porous titanium bracket sample in 50 ml acetone, ethanol, and deionized water respectively, treating it under ultrasonic conditions for 10 to 30 min, taking out the sample and rinsing it with deionized water; S22, acid erosion, 5~15mL·L -1 HF and 10~30mL·L -1 HNO3 is prepared into an acid leaching solution, HF:HNO3:H2O=1:4:5, the deoiled sample is placed in the acid leaching solution, cleaned under ultrasonic conditions for 20-40s, taken out and rinsed with deionized water under ultrasonic conditions to remove the residual acid on the surface, dried naturally and set aside; S23, preparation of anodizing electrolyte solution; S24. Preparation of TiO2 nanotube film by anodization.
7. The method for preparing a hierarchical porous structure cell adaptive growth bone repair scaffold according to claim 6, characterized in that: The preparation method of the anodizing electrolyte solution in step S23 is: Use a pipette to take 1-3 ml HF and 2-5 ml deionized water, add them to 90-95 ml diethylene glycol solvent, let the electrolyte stand for 10 minutes, stir it magnetically at 300-500 r / min for 30 minutes, mix the electrolyte thoroughly and evenly, and stabilize the temperature at 10-40°C.
8. The method for preparing a hierarchical porous structure cell adaptive growth bone repair scaffold according to claim 6, characterized in that: The method for preparing the TiO2 nanotube film by anodization in step S24 is: S241, using the SLM titanium implant as the working electrode and the platinum mesh as the counter electrode, immersing the sample in the electrolyte prepared in step 23 under the condition of a magnetic stirring speed of 300 to 500 r / min; S242, apply a constant potential of 40V to 100V, and anodic oxidation for 2h to 12h, and the experimental temperature is always stable at 10 to 40°C; S243. Rinse the surface of the sample obtained by anodization with deionized water for 10 to 15 times and dry it at 50 to 70°C.
9. The method for preparing a hierarchical porous structure cell adaptive growth bone repair scaffold according to claim 1, characterized in that: The step S3 specifically includes the following steps: S31, pretreatment, ultrasonication in acetone for 10 min, rinsing with deionized water three times, and drying at room temperature; S32, adjust the pH of type I collagen to neutral with glacial acetic acid, slowly add ALP solution, slowly stir for 30 minutes, and put the mixture with ALP solution into a dialysis bag, seal it and transfer it to a mixed solution of Ca-GP and CaCl2, Ca:P=1.67, after temperature change at 37°C, mineralize for 24h, 48h and 72h respectively, the collagen self-assembles into collagen fibers to form a gel; S33, the self-assembled type I collagen was ultrasonically cleaned with deionized water, and placed together with the SLM porous titanium scaffold in a homemade mold, and then placed in a -80°C refrigerator overnight, and freeze-dried in a freeze dryer to obtain a HAP-collagen-porous titanium scaffold; S34, adjusting the concentration of the collagen solution to control the porosity and pore size of the collagen fibers; S35. Use UV, XRD, XPS and FT-IR to detect the characteristic elements, crystal structure and groups of collagen and HAP in the porous titanium scaffold.
Citation Information
Patent Citations
Functionalized porous titanium metal bone implant material and preparation method thereof
CN107233619A
Gradient porous titanium mesh and preparation method of super-hydrophobic gradient porous titanium mesh
CN113020597A
Preparation method for 3D printing renewable functional gradient skeleton scaffold
CN114848921A
Method for constructing bionic nanostructure on surface of 3D printing titanium alloy implant
CN115958206A
Cited By
3D printing absorbable bone plug and preparation method thereof
CN120860308A
